Calculate optimum insulation thickness to all over Indian city and compare it with the degree day method. (5th January 2022) - Hasan, Shaheen; Khan, Sabah
The study is done on 60 cities from different climatic zones of India. Thermal insulation is an essential parameter in the building sector to save energy and money. This research focuses on using five insulation materials (extruded polystyrene, expanded polystyrene, glass wool, rock wool, and polyurethane). It investigates the effect of the insulation material's thermophysical properties in saving energy, life cycle cost, and payback period. The calculation is conducted using five different (coal, oil, gas, natural gas, and electric) fuels. The energy calculation is done using a heat balance algorithm. The results are compared and verified with the degree day method. EnergyPlus software is used to validate the results for the sixty cities selected. The difference in energy efficiency savings between these two methods is analysed to determine the potential error of each method.